Farmers do use mathematics: the case of animal feeding - Saló i Nevado, Laia; Holm, Gunilla; Pehkonen, Leila (NOMAD Nordic Studies in Mathematics Education, 2011)
This article presents findings from a study on the use of mathematics in the context of a farm. Ethnographic methods were used for the data collection and ethnomathematics provides the theoretical framework guiding the analysis. We present two different situations, as examples of ethnomathematics, in which the farmers make use of mathematics in daily life situations on a farm. The first situation has to do with how one of the farmers dealt with a barn as a space for feeding calves. The second situation is about the use of different objects as measuring tools.